The development of an audit procedure and treatment technologies for Rupert and Rothschild vignerons' winery wastewater - Marais, Dulcie (Stellenbosch : University of Stellenbosch, 2010)
Thesis (MScEng (Chemical Engineering))--University of Stellenbosch, 2001.